The iPREFACE score is useful for predicting fetal acidemia: A retrospective cohort study of 113 patients who underwent emergency cesarean section for non-reassuring fetal status during laborAJOG Global Reports at a Glance - Ayumu Ito, MD, PhD; Eijiro Hayata, MD, PhD; Hikari Kotaki, MD; Makiko Shimabukuro, MD; Mayumi Takano, MD, PhD; Sumito Nagasaki, MD, PhD; Masahiko Nakata, MD, PhD (Elsevier, 2024)
BACKGROUND: The iPREFACE score may aid in predicting fetal acidemia and neonatal asphyxia in emergency cesarean sections and vaginal deliveries, which may improve labor management precision in the future. OBJECTIVE: This study aimed to assess the use of the iPREFACE score as an objective indicator of the need for rapid delivery in cases of repeated abnormal waveforms without concurrent indications for immediate medical intervention during labor. STUDY DESIGN: This retrospective cohort study was conducted among term (37+ 0 days to 41+6 days) singleton pregnant women who underwent emergency cesarean section owing to a nonreassuring fetal status. The iPREFACE-DCS score, calculated from a 30-minute cardiotocography waveform before the decision to perform emergency cesarean section, and the iPREFACE-RCT score, calculated from a 30-minute cardiotocography waveform before cardiotocography transducer removal, were employed. The primary outcome was the assessment of the predictive ability of these scores for fetal acidemia, whereas the secondary outcomes were differences in umbilical artery blood gas findings and postnatal outcomes between the 2 groups, divided by the cutoff values of the iPREFACE-RCT score. RESULTS: The iPREFACE-DCS and iPREFACE-RCT scores demonstrated the capability to predict an umbilical artery blood pH of <7.2. The iPREFACE-DCS-RCT score, with cutoff values of 37 and 46 points, respectively, exhibited an area under the receiver operating characteristic curve of 0.82 and 0.87, respectively. The iPREFACE-RCT group with ≥46 points had higher incidence rates of an umbilical cord artery blood pH of <7.2, <7.1, and <7.0 and neonatal intensive care unit admissions for neonatal asphyxia. CONCLUSION: The iPREFACE score, derived from cardiotocography during an emergency cesarean section, may enable clinicians to predict fetal acidemia in cases of nonreassuring fetal status. Improved prediction of fetal acidemia and facilitation of timely intervention hold promise for enhancing the outcomes of mothers and newborns during childbirth. Prospective studies are warranted to establish precise cutoff values and to validate the clinical application of these scores.